2013
DOI: 10.1136/medethics-2012-100755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors that motivate participants to consent for non-therapeutic trials in India

Abstract: The most common motivating factor to participate in non-therapeutic studies appears to be different for healthy participants (financial reward) and patient participants (invitation to participate by the physician). Participants also felt that adequate information and care was given to them during the trial, and that they would participate in future clinical studies, and would also recommend such studies to their friends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 18 publications
(28 reference statements)
2
26
1
Order By: Relevance
“…These findings agree with findings of studies conducted in Brazil and India by Nappo et al (2013) as well as Doshi et al (2013). In situations of poor service delivery, medical care in a research setting is described in favorable terms.…”
Section: Discussionsupporting
confidence: 94%
“…These findings agree with findings of studies conducted in Brazil and India by Nappo et al (2013) as well as Doshi et al (2013). In situations of poor service delivery, medical care in a research setting is described in favorable terms.…”
Section: Discussionsupporting
confidence: 94%
“…In spite of this, only a fifth of the participants said they would allow their child to participate in a trial if there was a monetary benefit. This is contrary to what we found in a study in healthy adults [29] who participated in non-therapeutic clinical trials, where financial reward was the most common motivating factor for their participation.…”
Section: Discussioncontrasting
confidence: 99%
“…For example participant trust (in the institution, the researcher or the research protection system) has been indicated as an important condition of taking part as opposed to a reason for taking part [30-33]. A recent study in India examining motivation for participation in non-therapeutic clinical trials found that for patients it was the request from the treating physician that was the main motivating factor (88%), while financial reward was the main reason for 65% of the healthy participants who also reported free medical check up/personal health gains as important reasons (43%) [34]. …”
Section: Introductionmentioning
confidence: 99%